Minor China : method, materialisms, and the aesthetic - Yapp, Hentyle, 1980- (ANIMA (Duke University Press), 2021)
"Hentyle Yapp analyzes contemporary Chinese art as it circulates on the global art market to outline the limitations of the predominant narratives that currently frame understandings of non-Western art."--